RISIKO PEMBIAYAAN DALAM PERBANKAN SYARIAH - M Sholahuddin (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2004)
Bank of Shariah face risk of financing consisted of risk of financing Based on Natural CertaintyContracts and Natural Uncertainty Contracts. Unrighteous bank of Shariah have to own system ofobservation and management of taft risk. With this system, bank of Shariah law can detect and avoidthe happening of mismanagement and also failure of system and procedure [of] [at] Islamic bankingsystem, expected will minimize Non-Performing Financing (NPF) so that improve performance offinance of bank of Shariah and in the end improve competitive advantage of Shariah banking inIndonesia.